Development Strategies and the Status of Women A Comparative Sutdy of the United States, Mexico, the Soviet Union, and Cuba - Leahy, Margaret E. (Lynne Rienner Publishers, 2023)
Examines the effects of differing development strategies on women's political power, economic position, and social status in the United States, Mexico, the Soviet Union, and Cuba